PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Putri, Anggi Neisya Permata; Iswara, Ulfah Setia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research examined the effect of profitability, liquidity, and capital structure on firm value at Textile and Garment companies listed on IDX during 2019-2022; with firm size as a moderating variable. Return On Asset (ROA) measured profitability, current ratio measured liquidity, Debt to Equity Ratio (DER) measured capital structure, Price to Book Value measured firm value, and company size is measured using the natural logaritm (Total asset). The research was quantitative. Moreover, the data collection technique used purposive sampling. In line with that, there were 15 companies as the sample for 4 years. In total, 60 samples were analyzed. Furthermore, the data were secondary in the form of financial statements and annual reports taken from IDX. The results of the study indicate that profitability and capital structure have an effect on firm value, liquidity and firm size do not have an effect on firm value, firm size is able to moderate the effect of profitability and the effect of capital structure on firm value, while firm size is not able to moderate the effect of liquidity on firm value.